The Influence of Green Product, Green Advertising and Green Trust To The Purchasing decision of Skincare Himalaya Herbals in Palapa Department Store Surabaya - Nurul Hasanah; Wiwik Handayani (Trunojoyo University of Madura, 2020)
Global warming makes many cosmetics companies take advantage of this as an opportunity to create products that are environmentally friendly. To win the company's competition, it is necessary to have the right strategy so that the products created can be accepted and demanded by the public. This research is intended to analyze the effect of Green Product, Green Advertising, and Green Trust on Purchasing Decisions. The problem in this research is the less optimal consumer purchasing decisions on Himalayan Herbals products, because Most people have not been able to distinguish between Green Products with ordinary products and do not understand how important the use of Green Products for health and the environment. The purpose of this study was to determine the effect of Green Products, Green Advertising and Green Trust on Purchasing Decisions on Himalayan Herbals Skincare. The population in this study were Himalayan Herbals skincare customers in Palapa Toserba Surabaya. The sampling method used was non probability sampling with a purposive sampling technique and the total sample of 85 respondents. Data collection techniques through distributing questionnaires directly. Data analysis techniques using Partial Least Square (PLS). The results showed that the Green Product, Green Advertising, and Green Trust variables contributed to the Purchasing Decision. Global warming makes many cosmetics companies take advantage of this as an opportunity to create products that are environmentally friendly. To win the company's competition, it is necessary to have the right strategy so that the products created can be accepted and demanded by the public. This research is intended to analyze the effect of Green Product, Green Advertising, and Green Trust on Purchasing Decisions. The problem in this research is the less optimal consumer purchasing decisions on Himalayan Herbals products, because Most people have not been able to distinguish between Green Products with ordinary products and do not understand how important the use of Green Products for health and the environment. The purpose of this study was to determine the effect of Green Products, Green Advertising and Green Trust on Purchasing Decisions on Himalayan Herbals Skincare. The population in this study were Himalayan Herbals skincare customers in Palapa Toserba Surabaya. The sampling method used was non probability sampling with a purposive sampling technique and the total sample of 85 respondents. Data collection techniques through distributing questionnaires directly. Data analysis techniques using Partial Least Square (PLS). The results showed that the Green Product, Green Advertising, and Green Trust variables contributed to the Purchasing Decision. Abstraks Global warming membuat banyak perusahaan kosmetik memanfaatkan hal tersebut sebagai peluang untuk menciptakan produk yang ramah terhadap lingkungan. Untuk memenangkan persaingan perusahaan diperlukan adanya strategi yang tepat agar produk yang diciptakan dapat diterima dan diminati masyarakat. Penelitian ini dimaksudkan untuk menganalisis pengaruh Green Product, Green Advertising, dan Green Trust terhadap Keputusan Pembelian. Masalah dalam penelitian ini adalah kurang optimalnya keputusan pembelian konsumen terhadap produk Himalaya Herbals, karena Sebagian masyarakat belum bisa membedakan antara Green Product dengan produk biasa dan tidak memahami betapa pentingnya penggunaan Green Product bagi kesehatan dan lingkungan sekitar. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh Green Product, Green Advertising dan Green Trust terhadap Keputusan Pembelian pada Skincare Himalaya Herbals. Populasi dalam penelitian ini adalah Pelanggan skincare Himalaya Herbals di Palapa Toserba Surabaya. Metode pengambilan sampel yang digunakan adalah non probability sampling dengan teknik purposive sampling dan jumlah sampel sebanyak 85 responden. Teknik pengumpulan data melalui penyebaran kuesioner secara langsung. Teknik analisis data menggunakan Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa variabel Green Product, Green Advertising, dan Green Trust memberikan kontribusi terhadap Keputusan Pembelian.